2022
DOI: 10.33503/ebio.v7i01.1373
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of learning and motivation to use google classroom on critical thinking skills

Abstract: The effectiveness of learning is said to be successful if all learning can be fulfilled. One of them is learning motivation. Learning that can increase the effectiveness of learning and student motivation towards critical thinking skills is electronic learning with the google classroom application. E-learning can measure students' motivation to learn and their critical thinking skills. Students are considered successful when they achieve their learning goals. But in reality, students have not shown motivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Individuals with high critical thinking skills are more likely to address practical issues effectively (Hakim et al, 2018). Critical thinking skills refer to intellectual rigor involving the dynamic conceptualization utilization, analysis, evaluation, and communication of information derived from various sources, including experience, observation, reflection, and reasoning (Herlina & Syahfitri, 2022).…”
Section: Finding and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with high critical thinking skills are more likely to address practical issues effectively (Hakim et al, 2018). Critical thinking skills refer to intellectual rigor involving the dynamic conceptualization utilization, analysis, evaluation, and communication of information derived from various sources, including experience, observation, reflection, and reasoning (Herlina & Syahfitri, 2022).…”
Section: Finding and Discussionmentioning
confidence: 99%
“…The utilization of metacognitive skills has the potential to mitigate challenges encountered during the learning process. Additionally, critical thinking can offer thoughtful criticism as a component of the learning cycle, thereby enhancing students' capacity to resolve problems, identify influential factors, assess diverse possibilities, and arrive at informed decisions (Herlina & Syahfitri, 2022).…”
Section: Finding and Discussionmentioning
confidence: 99%
“…Previous studies have shown that general self-efficacy and learning approaches play a crucial role in developing critical thinking skills [34]. Digital learning tools such as Google Classroom can also influence critical thinking through self-regulated learning and learning motivation [35,36]. General self-efficacy may alter learning goals and self-assessments [37].…”
Section: Scenarios Of Ai Education Ai-related Technologymentioning
confidence: 99%
“…learning and learning motivation [35,36]. General self-efficacy may alter learning goals and self-assessments [37].…”
Section: Scenarios Of Ai Education Ai-related Technologymentioning
confidence: 99%
See 1 more Smart Citation